2021
DOI: 10.1017/ice.2021.281
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of Sofia Rapid Antigen Assay for detection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among emergency department to hospital admissions

Abstract: Objective To determine the utility of the Sofia® SARS rapid antigen fluorescent immunoassay (FIA) to guide hospital bed placement of patients being admitted through the emergency department (ED). Design Cross-sectional analysis of a clinical quality improvement study. Setting Two community hospitals in Maryland. From 9/21/2020 to 12/3/2020, 2887 patients simultaneously received the Sofia® SARS rapid antigen FIA and SARS-CoV-2 RT-PCR assays on admission through the ED. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Thus, the likelihood of false-negative antigen test results becomes higher at lower viral loads. While some studies detected no difference in the mean Ct values between symptomatic patients and asymptomatic patients [ 41 ], others reported that symptomatic patients displayed lower Ct values than asymptomatic COVID-19 patients, and a Ct value of 30 is the threshold for SARS-CoV-2 infectivity [ 22 , 38 ]. Moreover, it was shown [ 37 ] that different sensitivity versus Ct value patterns prevail in symptomatic and asymptomatic patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the likelihood of false-negative antigen test results becomes higher at lower viral loads. While some studies detected no difference in the mean Ct values between symptomatic patients and asymptomatic patients [ 41 ], others reported that symptomatic patients displayed lower Ct values than asymptomatic COVID-19 patients, and a Ct value of 30 is the threshold for SARS-CoV-2 infectivity [ 22 , 38 ]. Moreover, it was shown [ 37 ] that different sensitivity versus Ct value patterns prevail in symptomatic and asymptomatic patient groups.…”
Section: Discussionmentioning
confidence: 99%
“… (a) Cepheid’s Xpert Xpress SARS-CoV-2 test [ 39 ], (b) the work procedure of LabCorp COVID-19 test home collection kit [ 41 ], (c) Abbott’s ID NOW COVID-19 rapid test procedure [ 40 ], (d) Accula SARS-CoV-2 test [ 42 ], (e) Cue COVID-19 [ 43 ], (f) Sofia SARS Antigen FIA [ 44 ], (g) BD Veritor System for Rapid Detection of SARS-CoV-2 [ 45 ], and (h) Abbott BinaxNOW Antigen Self-Test [ 46 ]. FIA: fluorescent immunoassay.…”
Section: Resultsmentioning
confidence: 99%
“…To the Editor-We read with interest the article by Smith et al 1 describing the use of rapid antigen detection (RAD) for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) in guiding hospital admission triage. Given the rapid turnaround of pointof-care testing, various studies have utilized RAD tests at the point of entry into the healthcare system.…”
mentioning
confidence: 99%
“…Given the rapid turnaround of pointof-care testing, various studies have utilized RAD tests at the point of entry into the healthcare system. [1][2][3][4] However, most of these studies have occurred during periods of heightened transmission, with detection rates of 5%-21%. [1][2][3][4] RAD testing in clinical scenarios with lower incidence, such as asymptomatic individuals, may potentially result in low detection rates with high false-positive rates.…”
mentioning
confidence: 99%
See 1 more Smart Citation